The Impact of Institutional Structures on Transport Infrastructure Performance. A Cross-National Comparison on Various Indicators - De Jong, W. Martin (European Journal of Transport and Infrastructure Research, 2001)
It is generally acknowledged that structures and styles of decision-making have an important impact on what transport networks under these regimes look like. However, this has not been a regular line of research up to now. This paper investigates this by distinguishing four types of institutional structures that reflect various politico-administrative systems and styles in Western Europe. It seeks to construe an argument on how these types of institutional structures have divergent impacts on 1) decision-making speed on infrastructure projects, 2) satisfaction of actors in the decision making process, 3) Benefit-Cost ratios for projects, 4) modal split, 5) size of transport networks, 6) congestion in the networks and 7) investment levels. It seeks to explain why every specific type of institutional structure has a specific predicted impact on the form, type and performance of the transport networks and also takes into account that institutional structure is not the only factor with an impact on final physical outcomes. The article gives a well-substantiated argument on the supposed connection and provides some empirical evidence, but does not claim statistical significance. It sets a first step toward a new line of research and suggests this may prove fruitful as a contribution to policy making.